The Impact of Halal Supply Chain Integration on Quality Performance with Halal Production Practices as Mediation: A Study on Culinary SMEs in Pasar Gede Solo - Setyani, Lintang Ayu; Kusmantini, Titik; Widjanarko, Hendro (CV. Strata Persada Academia, 2025)
This study investigates the impact of Halal Supply Chain Integration (HSCI) on Quality Performance (QP) with Halal Production Practices (HPP) as a mediating variable, focusing on culinary SMEs operating in Pasar Gede Solo, Indonesia. Amid growing consumer awareness and regulatory requirements for halal compliance, the research explores whether HSCI directly improves QP or if the relationship is mediated by HPP. A quantitative descriptive design was employed, utilizing primary data collected from 52 SMEs through structured questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to test the measurement and structural models, ensuring reliability and validity through composite analysis, convergent validity, and discriminant validity. The results indicate that HSCI does not have a direct significant effect on QP, suggesting that halal compliance in the supply chain alone is insufficient to enhance product quality. However, HSCI has a significant positive effect on HPP, demonstrating that strong integration within the halal supply chain reinforces the implementation of halal procedures. Conversely, HPP does not significantly affect QP and does not mediate the relationship between HSCI and QP. These findings emphasize the need for SMEs to combine halal assurance with quality management systems to improve competitiveness. Practical implications include the importance of supplier collaboration, technical support from regulators, and consumer education on halal and quality standards. Future research is recommended to include additional variables such as product innovation and customer satisfaction to better explain quality performance outcomes.